Management of Human Rights-Friendly Priority Services for Vulnerable Groups at The Padang Class I Immigration Office With an Immigration Checkpoint - Mutiara Nurul Amalia; Yulia Hanoselina (PT Keberlanjutan Strategis Indonesia, 2026)
Abstract:Equitable access to public services remains a practical challenge for vulnerable groups because physical, communication, informational, and digital barriers may limit their ability to complete administrative procedures independently. This study analyzes the management of Human Rights-Friendly Priority Services for vulnerable groups at the Padang Class I Immigration Office with an Immigration Checkpoint and identifies the factors that support and hinder their implementation. The study employed a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving service managers, immigration officers, and service users from vulnerable groups. Data validity was assessed through source and technique triangulation, while analysis involved data reduction, data display, conclusion drawing, and verification. The analytical framework applied George R. Terry’s management theory through four indicators—planning, organizing, actuating, and controlling—and used Public Service Logic to interpret the value experienced by service users. The findings show that the Office has established a policy foundation, standard operating procedures, a dedicated service room, assistive facilities, staff coordination, direct assistance, internal evaluation, and complaint channels. These arrangements make passport services easier and more humane for older adults, pregnant women, breastfeeding mothers, and persons with disabilities. However, the service has not fully ensured independent and equitable access because tactile guiding paths are unavailable, sign-language competence is limited, staffing and service quotas are constrained during peak periods, waiting-room capacity is limited, and no satisfaction instrument specifically measures the experiences of vulnerable groups. The service therefore requires evidence-based planning, adaptive resource allocation, sustained staff training, accessible facilities, and user-specific evaluation.